Importance of regional competitiveness in transition economy - Павліха, Наталія Володимирівна; Кицюк, Ірина Василівна; Pavlikha, Nataliia V.; Kytsiuk, Iryna V. (University of Łódź, 2013)
The aim of the research is the theoretical and methodological justification of regional competitiveness in the conditions of transformation economy.

Nowadays, the successful involvement of Ukraine in world economic space in terms of further market-oriented transformation of the national economic system, acquiring the characteristics of the global knowledge economy, makes the relevance of competitiveness that is the key to its sustainable economic development. And, since the structural change of economy are showed mostly are the regional level that the first “react” to any reform, deepening of the process of market reforms in Ukraine makes it necessary to change stereotypes of management, planning methods and principles of management at the regional level.
Keywords: Region; Competitiveness; Transition Economy; Regional competitiveness